2007
DOI: 10.1038/ncb1602
|View full text |Cite
|
Sign up to set email alerts
|

BACE1 regulates voltage-gated sodium channels and neuronal activity

Abstract: BACE1 activity is significantly increased in the brains of Alzheimer's disease patients, potentially contributing to neurodegeneration. The voltage-gated sodium channel (Na(v)1) beta2-subunit (beta2), a type I membrane protein that covalently binds to Na(v)1 alpha-subunits, is a substrate for BACE1 and gamma-secretase. Here, we find that BACE1-gamma-secretase cleavages release the intracellular domain of beta2, which increases mRNA and protein levels of the pore-forming Na(v)1.1 alpha-subunit in neuroblastoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
324
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(339 citation statements)
references
References 46 publications
12
324
2
1
Order By: Relevance
“…57 In BACE1-transgenic mice and in temporal cortex of AD patients, increased BACE1 levels were found to be associated with enhanced b2 cleavage. 58 Moreover, that study revealed that the generated b2 intracellular domain acted as transcriptional activator for its Na v 1.1 a-subunit and increased Na v 1.1 protein, which was, however, retained intracellularly. Consistent with the findings in BACE1-over-expressing mice, Corbett et al…”
Section: Bace1 and Neuronal Na V Channelsmentioning
confidence: 99%
“…57 In BACE1-transgenic mice and in temporal cortex of AD patients, increased BACE1 levels were found to be associated with enhanced b2 cleavage. 58 Moreover, that study revealed that the generated b2 intracellular domain acted as transcriptional activator for its Na v 1.1 a-subunit and increased Na v 1.1 protein, which was, however, retained intracellularly. Consistent with the findings in BACE1-over-expressing mice, Corbett et al…”
Section: Bace1 and Neuronal Na V Channelsmentioning
confidence: 99%
“…In addition to APP, a number of other putative BACE1 substrates have been identified, including neuregulin (NRG1; Lindholm et al, 2002;Wong et al, 2005), voltage-gated sodium channel (VGSC; Na v ) subunits Kim et al, 2007), lipoproteinlike receptor related protein (LRP; von Arnim et al, 2005), amyloid precursor-like proteins (APLP; Li and Sudhof, 2004;Pastorino et al, 2004), P-selectin glycoprotein ligand 1 (PSGL-1; Lichtenthaler et al, 2003) and beta-galactoside alpha 2,6-sialyltransferase (ST6Gal I; Kitazume et al, 2005). Importantly, many of these substrates may play a role in neuronal function (NRG1, VGSCβ subunits) and the cellular response to stress and/or injury, such as recovery from excitotoxicity (Aβ; Kamenetz et al, 2003), Aβ clearance (LRP; Hyman et al, 2000), synapse formation (APP, APLP1, APLP2; Herms et al, 2004;Wang et al, 2005) and immune functions (PSGL-1, ST6Gal I; Lichtenthaler et al, 2003;Kitazume et al, 2005).…”
Section: Cellular Changes Associated With Vascular Diseases Can Elevamentioning
confidence: 99%
“…However, characterization of BACE1 substrates other than APP (including the voltage-gated sodium channel Na(v)1 ␤2-subunit and neuregulin 1) pointed out the role of BACE1 in neuronal functions (24,25). Studies analyzing BACE1 knockout mice indeed highlighted dysfunctions in synaptic transmission and plasticity (26 -28).…”
mentioning
confidence: 99%